Risk of substance use disorders among adolescents and emerging adults with type 1 diabetes: A population‐based cohort study. Issue 8 (30th September 2021) - Creo, Ana; Sriram, Swetha; Vaughan, Lisa E.; Weaver, Amy L.; Lteif, Aida; Kumar, Seema
Abstract: Background: Adolescents and emerging adults with chronic health conditions such as type 1 diabetes mellitus (T1D) are more likely to engage in high‐risk behaviors. Previous studies regarding substance use in adolescents and emerging adults with T1D are mostly derived from cross‐sectional studies utilizing self‐administered questionnaires and are limited by lack of population‐based comparison groups. In addition, despite the rising popularity of vaping, little is known about the incidence of vaping in adolescents and emerging adults with T1D. Methods: We explored the incidence and prospective risk of substance use disorders (SUD) and vaping in adolescents and emerging adults with T1D compared to age and gender matched nondiabetic referents residing in Olmsted County, Rochester, MN. Results: Risk of incident SUD was higher in those with T1D compared to matched referents with alcohol, marijuana, and smoked tobacco being most common substances. When stratified by gender, these differences remained significant in males, but not females. Conclusions: While further work is needed to delineate the causative relationships between T1D, mental health, and substance abuse, our findings confirm the critical need for substance use screening and mental health support for adolescents and emerging adults with T1D.